The Birth of the Cult of St Menas - Wipszycka, Ewa (Vox Patrum, 2025)
It is not necessary to go through all the stages of initiation into the intricacies of hagiographical studies to immediately recognize, when reading the works related to the dossier of St Menas, that we are dealing with a subgenre of hagiography which contemporary scholars term “fictional hagiography”. The figure of the Saint and the events of his life were invented by anonymous authors and editors in various ways, according to their own tastes and the anticipated tastes of their audience. This article seeks to identify the narrative elements, terms, and descriptions of events that serve as markers of this specific genre. My aim is not to reconstruct the biography of the saint, but to gain a better understanding of the religiosity of those who came to Abū Mīnā, particularly their expectations. Researchers of the St Menas dossier are fortunate to have at their disposal extensive findings from archaeological excavations, which enable not only the dating of the sanctuary’s establishment and expansion but also aid in reconstructing the spaces and buildings where the cult of the Saint took place. While literary texts require ongoing critical assessment of their reliability, the extensive sanctuary, its furnishings, churches, houses, and streets relieve us from an excessive level of skepticism. Although the article’s title suggests a focus on texts, archaeology assists the historian in creating a comprehensive picture of what occurred at Abū Mīnā.